Tocilizumab for refractory organising pneumonia associated with Sjögren's disease. (14th May 2015) - Justet, Aurelien; Ottaviani, Sebastien; Dieudé, Philippe; Taillé, Camille
Abstract : Lung involvement in primary Sjögren syndrome occurs in approximately 10–20% of patients. Tocilizumab, an anti-interleukin-6 receptor antibody, has demonstrated efficacy and safety in small series of systemic sclerosis, and systemic lupus erythematosus, but its effect on interstitial lung manifestations of connective tissue diseases is not well known. We report the use of tocilizumab in a refractory organising pneumonia associated with Sjögren's disease. Our observation suggests that tocilizumab could be an alternative therapeutic in refractory organising pneumonia.